Supporting Open Innovation Behaviors in Researchers: Developing a Training with Acceptance and Commitment Training - Clio Dosi; Ettore Gorni; Matteo Vignoli; Silvia Cau; Giovambattista Presti (CERN IdeaSquare Journal of Experimental Innovation)
This study explores the use of Acceptance and Commitment Training (ACT) to overcome individual-level barriers to open innovation in academic and research environments. Rooted in the management literature on Not Invented Here and Not Shared Here biases, the research examines how rigid professional identities obstruct knowledge exchange and interdisciplinary collaboration. Although perspective-taking has been identified as a promising method for mitigating these biases, actionable interventions remain scarce, particularly in scientific contexts. To address this gap, we developed and iteratively refined a two-day training intervention using an Action Research Innovation Management Framework. The intervention integrates ACT principles to enhance perspective-taking and promote open innovation behaviors among researchers. Findings demonstrate that ACT is effective in reducing cognitive biases related to knowledge flows. The results also highlight the critical role of perspective-taking in facilitating the adoption of open innovation practices within academic settings. The study provides practical implications for university administrators and Knowledge Transfer Offices, emphasizing the need to address psychological barriers alongside structural incentives to enable more effective implementation of open innovation initiatives.